Effectiveness of Flipchart Media in Improving Mothers’ Knowledge of Child Growth and Development in Lebak District, Indonesia - Kadar Kuswandi; Nintinjri Husnida; Melly Halimatussa'adiah (Gema Lingkungan Kesehatan, 2026)
This study aims to analyse the effectiveness of flipcharts compared to the KIA Book in improving mothers’ knowledge of child growth and development at Posyandu clinics. The study employed a mixed methods convergent design using a quasi-experimental pre-test–post-test two-group design and in-depth interviews with health workers. Quantitative data were collected using a 20-item questionnaire on child growth and development knowledge from 18 mothers of toddlers, divided into a flipchart group and a KIA Book group, whilst qualitative data were obtained through semi-structured interviews. Data analysis utilised the Shapiro–Wilk test, the Wilcoxon Signed Rank Test, the Independent Samples t-test, gain score analysis, and ANCOVA, whilst effect sizes were reported using Cohen’s d and the standardised mean difference (SMD). The results of the study showed that the flipchart group experienced a greater increase in knowledge compared to the MCH Book group, with a large effect size (Cohen’s d = 1.06). Interview results indicated that health workers considered the flipchart to be more practical, communicative, user-friendly, and visually appealing compared to the KIA Book. The integration of quantitative and qualitative results suggests that the flipchart medium is more effective in supporting child growth and development education based on Posyandu in rural communities and has the potential to strengthen the implementation of Posyandu Reform through a more contextually appropriate health communication approach.